Consumidor Innovador, ¿Tiene Relación Con La Lealtad A La Marca? - Ruiz, Edith Reyes; Siller, Jesús Francisco Mellado; Wong, Adriana Méndez (European Scientific Journal, ESJ, 2017)
Consumer behavior establishes a relationship between living level and the consumer material resources with the characteristics of innovation. This, however, is considered to be of significant importance to companies based on the needs of the market and the business environment. In the field of marketing, it is essential to know the market and there is a need to investigate the behavior for the selection of clothing. A study was carried out with the Chengedzai scale in the city of Saltillo, Coahuila, Mexico. It is an empirical investigation which concludes on two important aspects: loyalty to the brand that makes it possible for clothing consumers to generate a measurement of reasons for the consumers of clothing for innovation and the application of products, processes, and marketing innovation in its application in distribution systems.